A Protocol for Implementing the Interim Population Consequences of Disturbance (PCoD) Approach : Quantifying and Assessing the Effects of UK Offshore Renewable Energy Developments on Marine Mammal Populations /: Quantifying and Assessing the Effects of UK Offshore Renewable Energy Developments on Marine Mammal Populations. (February 2014) - (Professor in marine biology), Harwood, John; (Lecturer in animal communication), King, Stephanie; Schick, Rob; Donovan, Carl; Booth, C. G (Cormac G.)
No abstract available